The redescription of three species of Sicyonella (Crustacea: Decapoda: Dendrobranchiata: Sergestidae) - Fukuoka, Kouki; Tamaki, Motoya; Kikuchi, Tomohiko (Zootaxa, 2005)
Three species of Sicyonella, S. antennata, S. inermis, and S. maldivensis, were redescribed and illustrated in detail. In addition to characters of the antennular peduncle and petasma, the three species are distinguished by the shape and armature of the proximal part of the mesial antennular flagellum of the male, the color of the antennal flagellum, the number and size of spiniform setae on the distomesial corner of the sympod of the second, third, and fifth pleopods, and the shape of the thelycum. On the basis of these characters, a female of the syntype of S. maldivensis from Mauritius was identified as S. inermis. Therefore, a male of the syntype from the Maldives is designated the lectotype of S. maldivensis.